"A Ditcher and a Scholar": Figuring College-Going Identities in an Urban Magnet High School. Issue 1 (January 2019) - Duncheon, Julia C.; Relles, Stefani R.
Background/Context: To enhance postsecondary completion and minimize equity gaps, researchers have focused on defining, measuring, and developing students' college readiness, or the preparation required to persist in higher education. While this work has been useful to identify the ingredients of postsecondary success, the emphasis on individual achievement runs the risk of portraying marginalized students as deficient. Culturally relevant studies that highlight institutional accountability for college readiness are needed to inform policy and practice. Purpose/Objective/Research Question/Focus of Study: Using Holland and colleagues' (1998) figured worlds theory, this study examines college readiness through the lens of student identity in an urban magnet high school. We investigate how first-generation, low-income students of color interpreted and negotiated local discourses and artifacts to "figure" college-going identities—that is, who they should become and how they should behave to earn a college degree. The purpose of this empirical approach is to contribute information that can inform college readiness efforts nationwide. Research Design: The study utilizes an ethnographic approach that focused on how students conceptualized and developed their identities within the figured world of the magnet school. Data collection took place over the course of one school year and included over 200 hours of participant observation, in-depth interviews with 25 students and school staff, and document analysis. Findings: The figured world of Jackson Magnet fostered and reinforced a hierarchy that consisted of magnet students ("scholars") and their counterparts in the regular school ("ditchers"). A local feedback loop implied that the magnet school provided more rigorous college preparation than the regular school and, by extension, magnet students figured they would be ready for college. However, real-world feedback (standardized test scores) suggested magnet course rigor did not accurately reflect postsecondary standards. The result was that magnet students were underprepared but did not know it, an outcome that positioned them to experience a drastic identity reckoning in college. Conclusions/Recommendations: While most college-readiness research focuses on academic skills preparation, our findings reveal the need to consider how high schools prepare students in terms of identity. In particular, our data suggest the threat of well-intentioned achievement discourses on pre-college identity development. Salient questions include whether and how to increase postsecondary opportunity without socializing students either to discriminate against their peers or to figure a false identity that undermines preparation and future cognitive stability.